Terra nullius: A possessed landscape - Costantino, Thea (Inter-Disciplinary.Net, 2012)
Australia has long been described as an empty space and a site of monstrous inversion. As is well known, the British colonised the Australian continent under the legal dictum of terra nullius—land belonging to no one. This fiction conceals the ancient history of prior settlement by Indigenous Australians and enabled the invading forces to appropriate their lands. In the postcolonial and multicultural Australia of today, several conflicting views of land, home and history continue to exist simultaneously. In this climate, the land itself has become both a symbol and battleground for competing views of history and home. The image of virgin, unpopulated wilderness that is evoked by the phrase ‘terra nullius’ persists as a powerful signifier in Australian culture. It is an unstable symbol, however, having been co-opted both in support of white nationalist mythology and as a motif which expresses doubts about the legitimacy of European settlement and the socially exclusive construction of national space. The image of the Australian landscape as a site of emptiness, a negative space haunted by an unseen presence that threatens to consume the outsider, repeatedly appears as a monster of the colonial imagination. In such visions, the familiar landscape of home is transformed by the Freudian uncanny into something alarmingly alien. Such unhomeliness, or perhaps homelessness, makes repeated incursions into Australia’s self-representations. This chapter argues that representations of the Australian landscape as an empty and hostile space are linked to questions of colonial legitimacy and belonging. Contemporary artists in Australia continue to explore this recurring theme, and in doing so tease at a history of possession and dispossession.